PENGARUH DOSIS PUPUK ORGANIK CAIR BONGGOL DAN KULIT BUAH PISANG KEPOK TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) - Sarimunah Sarimunah; Zairin Zairin; Yudhi Ahmad Nazari (Agroekotek View, 2019)
Onion plant are horticultural commodities and include spices, these vegetables are used every day as a complement to spices to increase the taste and enjoyment of food. The increasing consumption of onion must be balanced with increased production. One way is to give liquid organic fertilizer hump and kepok banana peel. Hump and kepok banana peel contain nutrients that have the potentiali to be used as food sources so that microbes are well developed and have nutrient and nutrient content in them. Theiresearch aim knowing influence of the type material and dosage of liquid organic fertilizer hump and kepok banana peel on the growth and results of onion plant. Research design Factorial Completely Randomized Nested Design consisting of 2 factors, factor A type of material there are 2 types, namely a1 = hump and a2 = peel, factor B dosage is 5 levels, b0 = control, b1 = 50, b2 = 100, b3 = 150 and b4 = 200 ml.Plant-1. The type of material liquid organic fertilizer hump and kepok banana peel did not have an effect on all observations, but the dosage liquid organic fertilizer hump and kepok banana peel had an effect on plant height aged 21, 28 and 35 hst, the number of leaves aged 21 and 28 hst and number of tillers aged 28,,42 and 55 hst. The best dosage of the type material hump in plant height aged 21, 28 and 35 hst, the number of leaves aged 21 hst and the number of tillers aged 28 hst and the type material peel material in plant height aged 28 hst and the number of tillers aged 28 and 42 hst dosage is 100 ml.plant-1. The best dosage of the type material in the number of leaves aged 28 hst and number of tillers aged 42 and 55 hst and the type material peel material in plant height aged 21 and 35 hst, numberi of leaves aged 21  hst and number of tillers aged 55 hst dosage is 50 ml.plant-1.